Heterogeneity of capital structure adjustment speed across Industry sector: Evidence from non-financial firms in Malaysia. - Chua, Mei-Shan; Wahab, Noor Maimun Abdul; Roslen, Siti Nurhidayah Mohd; Chuah, Soo-Cheng; Nizar, Nurhuda; Chin, Hon-Choong (The Indonesian Capital Market Review, 2024)
This study investigates the speed of adjustment (SOA) to target leverage for different industry sec- tors in Malaysia. Using the two-step system generalized method of moments for 415 non-financial firms from 2010 to 2021, we found that the SOA for the overall sample is 38.6% and 22.0% for total debt and long-term debt, respectively. Our paper reveals the heterogeneity of SOA based on industry sectors. The industrial sector has the slowest adjustment speed (14.1%), whereas the healthcare in- dustry has the quickest adjustment speed (80.4%) to target leverage. Our results are consistent with the dynamic capital structure theory regarding the deviation between target and actual leverage. Fur- thermore, our study demonstrates the significance of an industry-based perspective when researching SOA, which suggests that the capital structure strategy depends on the industry's business climate.